The Antigastric Cancer Effect of Triptolide is Associated With H19/NF-κB/FLIP Axis - Yuan, Weiwei; Huang, Jinxi; Hou, Shanshan; Li, Huahua; Bie, Liangyu; Chen, Beibei; Li, Gaofeng; Zhou, Yang; Chen, Xiaobing (Frontiers in Pharmacology, 2022)
Background and Objective: Triptolide (TP), one of the fat-soluble components extracted from the Chinese medicinal herb Tripterygium wilfordii Hook F. (TWHF), possesses strong antitumor bioactivities, but its dose-dependent side effects restrict its wide application. This study was designed to investigate whether inflammatory factors increased the antitumor effects of the nontoxic dose of TP on gastric cancer cells and tried to explore the possible molecular mechanisms. Method: AGS and MKN45 cells were treated with different doses of TP and TNF-α. Cell viability and apoptosis were detected in vitro. In addition, NF-κB mediated prosurvival signals and cytoprotective proteins, especially FLICE-inhibitory protein (FLIP), were detected to determine their effects on TP/TNF-α–induced apoptosis. Moreover, the function of lncRNA H19/miR-204-5p/NF-κB/FLIP axis was investigated in vitro, and the antigastric cancer effect of TP plus TNF-α was proved in the mice xenograft model. Result:In vitro experimental results showed that TP pretreatment promoted apoptosis in AGS and MKN45 cells upon TNF-α exposure. TP/TNF-α–mediated apoptosis was partly mediated by the inhibitory effect of NF-κB–mediated FLIP expression. Oncogene H19 lying in the upstream pathway of NF-κB played a vital role upon TNF-α exposure, and bioinformatics analysis proved that H19 participated in TP/TNF-α–induced apoptosis via binding of miR-204-5p. Lastly, a low dose of TP and TNF-α inhibited the tumor weight and tumor volume of AGS and MKN45 cells in vivo. Conclusion: TP pretreatment increased apoptosis in TNF-α–stimulated gastric cancer cells, which are dependent on the disruption of the H19/miR-204-5p/NF-κB/FLIP axis. Cotreatment of TP and TNF-α is a better option for enhancing the anticancer effect and lowering the side effect of TP.